Can Art Make a Difference? Visual and Performative Arts on the Subject of Indonesian Mass Killings of 1965–66 - Michał Bielecki (Center for Southeast Asian Social Studies (CESASS), 2018)
This paper considers the impact of various activities of artistic nature in public debate and collective memory of the genocide in Indonesia in the years 1965-1966, as well as the public reception of these event, with a particular focus on Joshua Oppenheimer’s documentary „The Act of Killing” (2012). As a result of systematic extermination of PKI members and sympathizers, between 500 thousand and 2 million people were killed. These murders are often considered an ‘unspoken’ or ‘forgotten’ crime. In Suharto’s Indonesia, questioning the official version of events was prohibited. In 1998, General Suharto resigned from office and the state begun a slow drift towards democracy. The issue of the traumatic past, however, remains a very uncomfortable one. The crime of such scale cannot be easily forced into oblivion. The pressure faced by authorities in today's Indonesia was caused partly, if not mainly, by mnemonic actors of an artistic nature, by both Indonesian and foreign artists interested in this matter. By applying content analysis, the proposed paper discusses varied artistic activities addressing the mass violence and their influence on the public discussion and the collective memory of that event. The analysis of media reports, interviews with artists, fictional and documentary films was carried out by the author. The study shows how art contributes to the process of dealing with Indonesia’s past.